(untitled) (Fiep Bulletin - online, 2017)
The internship represents an unpaired opportunity to the academic formation, for being a moment in which the studentwill know their field and still have de freedom to work in their area of training. In the supervised internship I of the degree course ofphysical education this experience is proposed with the classes related to the kindergarten, opening a range of opportunities inthis educational level. Before that, this study aims to describe a report over this experiences acquired during the internship held atSchool Sesc – Unit Mossoró/RN, regarding the supervised internship I given the degree course of physical education –UERN/FAEF, being a descriptive qualitative study. Given those experiences we could perceive the differences in the behaviorcharacteristic of the age groups of each of the participating classes, as well as to reaffirm the importance of physical education forsuch students. We conclude by this that physical education is beyond classes poorly planned and without context, its importancecan be expressed by content sources with a view to enriching the motor learning process, cognitive, emotional and socialdevelopment of students.